KAJIAN YURIDIS PERJANJIAN KERJA SAMA SISTER CITY ANTARA KOTA BANDUNG DENGAN KOTA SEOUL TENTANG PEMBENTUKAN KERJASAMA KOTA - Hana Aulia (Faculty of Law Universitas Sebelas Maret, 2024)
This research raise issues regarding the status of the Sister City Cooperation Treaty Between Bandung City and Seoul City based on international law and the obstacles faced and solutions to solve the problem in its making. The method used in this research is a normative legal research and prescriptive research. The types and sources of research data used are primary legal materials and secondary legal materials that are collected by collecting legal materials from literature studies. The data analysis technique used is the deductive mindset technique. This research results that the status of the Sister City Cooperation between Bandung City and Seoul City based on international law is a treaty based on the 1969 Vienna Convention and Law Number 24 of 2000 concerning International Treaties. The obstacles faced are; (1) budget constraints with solutions to create a special budget and receive grant assistance; (2) commitment constraints with solutions in the form of utilizing existing technology; and (3) communication constraints with solutions in the form of short training of staff that will be on duty.